Serology and longevity of immunity against Echinococcus granulosus in sheep and llama induced by an oil‐based EG95 vaccine - Poggio, Thelma Veronica (2016)
An oil‐based formulation of the EG95 vaccine to protect grazing animals against infection with Echinococcus granulosus was formulated in Argentina. The efficacy of the vaccine was monitored by serology in sheep and llama (Lama glama) and was compared to the serology in sheep previously published using a QuilA‐adjuvanted vaccine. Long‐term efficacy was also tested in sheep by challenging with E. granulosus eggs of the G1 strain 4 years after the beginning of the trial. The serological results for both sheep and llama were similar to those described previously, except that there was a more rapid response after the first vaccination. A third vaccination given after 1 year resulted in a transient boost in serology that lasted for about 12 months, which was similar to results previously described. Sheep challenged after 4 years with three vaccinations presented 84·2% reduction of live cysts counts compared with control group, and after a fourth vaccination prior to challenge, this reduction was 94·7%. The oil‐based vaccine appeared to be bio‐equivalent to the QuilA vaccine.